Deleuze and Contemporary Art - Zepke, Stephen; O'Sullivan, Simon (Edinburgh Edinburgh University Press, 2011)
What is at stake for contemporary art in the take up of Deleuze and Guattari's thought? What are the limits and possibilities of this take up? To address these questions, this book presents a series of inflections that explore the connection between these two fields. The topics studied range from the political and the expanded 'aesthetic paradigm' of art practice today, to specific scenes and encounters and the question of technology in relation to art.These essays have been written by philosophers and artists working at the cutting edge of this new area, including writers from outside the Anglo-American tradition. The contributors include Gustavo Chirolla Ospina, Suely Rolnik, Gerald Raunig, Eric Alliez, Maurizio Lazzarato, Jussi Parikka, Johnny Golding, David Burrows, Robert Garnett, Edgar Schmitz, Claudia Mongini, Elisabeth von Samsonow, Barbara Bolt, Neil Chapman and Ola Stahl.